Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pengguna Berdasarkan Metode Webqual 4.0 Pada Website Stikom Career Center (SCC) Surabaya - Alhidayah Jamalludin; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Stikom Career Center is one part that is in Stikom Surabaya which serves to career development, which is under the Vice Chancellor for Student Affairs and Alumni. Stikom Career Center officially have a website with the address scc.stikom.edu as a means to share information and act as a mediator between companies / institutions / industries job seekers and job seekers, especially those who come from the alumni Stikom Surabaya to seek employment information. During the service was implemented has not been done an evaluation of the quality of the website is based on the perception of the end user as feedback to party business website (Management) so that users become dissatisfied with the services of the website itself. The purpose of this study was to look into the matter by analyzing the relationship between the quality of the website (Website Quality) and user satisfaction (User Satisfaction) with 4.0 WebQual method that has Usability, Information quality and Service Interaction. Distributing questionnaires conducted obtained a sample of 75 respondents. Data from the questionnaire testing the variables with the validity and reliability, test assumptions to the multiple linear regression . The conclusion of the study is that there is the effect of variable Usability and Information Quality on User Satisfaction. This means that the increase can be carried out on each indicator variable that has the lowest average. Usability improvement for more emphasis on Display website, while for Information Quality improvement by managers can be emphasized at the complete information so that users become more satisfied.Keywords: Webqual 4.0, Usability, Information Quality, Service Interaction, Multiple Linear Regression.